External ventricular drainage combined with continuous lumbar drainage in the treatment of ventricular hemorrhage - Xia D; Jiang X; Li Z; Jin Y; Dai Y (Therapeutics and Clinical Risk Management, 2019)
Dayong Xia,1 Xiaochun Jiang,1 Zhenbao Li,1 Yuelong Jin,2 Yi Dai11Department of Neurosurgery, The First Affiliated Hospital of Wannan Medical College, Wuhu 241000, Anhui Province, People’s Republic of China; 2School of Public Health, Wannan Medical College, Wuhu 241000, Anhui Province, People’s Republic of ChinaObjective: Intraventricular hemorrhage (IVH) is characterized by acute onset, rapid progression, and high disability and mortality rates. In this study, we investigated the clinical effect of external ventricular drainage combined with continuous lumbar drainage in IVH treatments.Methods: 114 patients with IVH treated at the Department of Neurosurgery, First Affiliated Hospital of Wannan Medical College from January 2015 to December 2017, were included in the study. Based on the different surgical methods, patients were divided into control (n=79) and study groups (n=35). The control group was treated with external ventricular drainage, whereas the study group was treated with external ventricular drainage combined with continuous lumbar drainage. The incidence of intracranial infection and hydrocephalus was compared between the two groups. The Glasgow coma scale (GCS) and the Glasgow outcome scale (GOS) were compared between the two groups 7 days postoperatively and at follow-up visits, respectively.Results: The incidence of intracranial infection and hydrocephalus in the study group was significantly lower compared with those in the control group (P<0.05). Seven days postoperatively, the GCS score of the study group was significantly higher than that of the control group (P<0.05). At the 3-month follow-up visit, the GOS score of the study group was higher than that of the control group (P<0.05).Conclusions: Using external ventricular drainage combined with continuous lumbar drainage can reduce the incidence of intracranial infection and hydrocephalus and improve the prognoses and quality of life in patients with IVH.Keywords: intraventricular hemorrhage, external ventricular drainage, continuous lumbar drainage, intracranial infection, hydrocephalus